Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1097/mpa.0b013e3181bae9b3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prognostic Factors in Metastatic Tumors of the Pancreas

Abstract: There may be a subset of patients with pancreatic metastases who are able to benefit from surgery with respect to improved long-term survival. Symptoms at diagnosis, presentation with primary tumor, surgical resection, and pathologic diagnosis seem to be important prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 41 publications
4
72
0
1
Order By: Relevance
“…The 1-year survival rates for such patients from the AJCC melanoma staging database is 41%. Perhaps even more controversial is the resection of multiple organ-site disease [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1-year survival rates for such patients from the AJCC melanoma staging database is 41%. Perhaps even more controversial is the resection of multiple organ-site disease [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al [10] retrospectively analyzed 47 patients who underwent thoracotomy for lung metastases from malignant melanoma. They demonstrated that, in selected patients, thoracotomy with complete excision of the metastatic deposits results in improved survival and should be considered the treatment of choice (the overall 5-year survival rate was 25% with a median survival of 19 months).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, despite these radiological features, it can be difficult to distinguish a pancreatic RCC metastasis from a primary pancreatic ductal and lesions should be evaluated with biopsy [22, 23]. There are several factors affecting survival of patients with metastases of RCC: the site and number of foci, the performance status and the disease free interval of the patients [24, 25]. Pancreatic metastasectomy of RCC was reported to improve survival in selected patients [4–7].…”
Section: Discussionmentioning
confidence: 99%
“…2 Masetti et al analyzed the prognostic factors relating to metastatic tumors in the pancreas and found two and five-year survival rates of 57.1% and 34.3% in cases of pancreatic metastasis due to breast cancer, respectively. 28 Surgical resection in cases with disease limited to the pancreas is considered to be the main form of treatment, despite its morbidity.…”
Section: Discussionmentioning
confidence: 99%